Dietary iron loading negatively affects liver mitochondrial function. Issue 11 (13th October 2017) - Volani, Chiara; Doerrier, Carolina; Demetz, Egon; Haschka, David; Paglia, Giuseppe; Lavdas, Alexandros A.; Gnaiger, Erich; Weiss, Guenter
Abstract : Dietary iron overload affects liver metabolic homeostasis, reducing mitochondrial respiratory capacity, and increasing reactive oxygen species (ROS) production, in a strain-dependent manner. Abstract : Iron is an essential co-factor for several metabolic processes, including mitochondrial respiration, and mitochondria are the major sites of iron-utilization. Cellular iron homeostasis must be tightly regulated, as intracellular iron deficiency can lead to insufficient energy production, whereas iron overload triggers ROS (reactive oxygen species) formation via the Fenton reaction. So far little is known on how iron imbalances affect mitochondrial function in vivo and the impact of the genotype on that, we studied the effects of dietary iron loading on mitochondrial respiratory capacity in liver by comparing two genetically divergent mouse strains, namely C57BL/6N and FVB mice. Both mouse strains differed in their basal iron levels and their metabolic responses to iron loading as determined by expression of iron trafficking proteins (ferritin was increased in livers of animals receiving high iron diet) as well as tissue iron content (2-fold increase, FVB p = 0.0013; C57BL/6N p = 0.0022). Dietary iron exposure caused a significant impairment of mitochondrial oxidative phosphorylation, especially regarding OXPHOS capacity (FVB p = 0.0006; C57BL/6N p = 0.0087) and S-ETS capacity (FVB p = 0.0281; C57BL/6N p = 0.0159). These effects were more pronounced in C57BL/6N than in FVB mice and were paralleled by an iron mediated induction of oxidative stress in mitochondria. The increased susceptibility of C57BL6/N mice to iron loading may be due to reduced expression of anti-oxidant defense mechanisms and altered iron trafficking upon dietary challenge pointing to a role of genetic modifiers for cellular and mitochondrial iron trafficking. Finally, iron-mediated induction of mitochondrial oxidative stress and reduction of oxidative phosphorylation may underlie fatigue in subjects with iron loading diseases.